A re-investigation of the Fries rearrangement of 3-chlorophenyl acetate and synthesis of 2-azido-1-(4-(benzyloxy)-2-chlorophenyl)ethanone from 4-bromo-3-chlorophenol. Issue 51 (20th December 2017) - Procopiou, Panayiotis A.; Coe, Diane M.; Procopiou, George
Graphical abstract: Highlights: A re-examination of the Fries rearrangement of 3-chlorophenyl acetate. Synthesis of 4-benzyloxy-2-chlorophenacyl azide. 2, 4-Diacetyl resorcinol. Abstract: The Fries rearrangement of 3-chlorophenyl acetate provided the expected 4-chloro-2-hydroxy-acetophenone as the major product and 2, 4-diacetyl resorcinol and 2-chloro-4-hydroxy-acetophenone as minor products. 4-Benzyloxy-2-chloroacetophenone was prepared by a Heck reaction and then elaborated to 4-benzyloxy-2-chlorophenacyl azide.